High fidelity [videorecording (DVD)] - Frears, Stephen; Cusack, John, 1966-; Black, Jack, 1969-; Bonet, Lisa, 1967-; Cusack, Joan, 1962-; Gilbert, Sara, 1975-; Hornby, Nick (Touchstone Home Video : Distributed by Buena Vista Home Entertainment, 2000)
Rob Gordon's record store is semi-failing, and his long-time girlfriend has just walked out on him. In order to figure out where things went wrong, he examines his past relationships with other women.